Ethical Dilemmas Using Social Media in Qualitative Social Research: A Case Study of Online Participant Observation. (September 2020) - Hennell, Kath; Limmer, Mark; Piacentini, Maria
Social media platforms that enable users to create and share online content with others are used increasingly in social research. This article explores the complex ethical issues associated with using social media for data collection, drawing on a study of the alcohol consumption practices of young people. It aims to contribute to debates about the practical and ethical challenges facing researchers using social media as a data collection tool, and to demonstrate how a reflexive approach to the research and the context in which the research takes place is critically important for supporting and enabling an ethical approach. The article concludes by recommending that researchers who face ethical dilemmas associated with the use of social media maintain an ongoing dialogue with their relevant ethics committees and other researchers to identify potential solutions and to share their findings.